Highly dense cellulose acetate specimens with superior mechanical properties produced by fused filament fabrication. (24th April 2020) - Böhler, Stefan; Bartel, Melanie; Bohn, Andreas; Jacob, Ron; Ganster, Johannes; Büsse, Thomas; Balko, Jens
Abstract: The extrusion based Fused Filament Fabrication (FFF) enables to build up components of thermoplastic materials by using a layer-by-layer strategy. Typically, the layered structure results in an internal porosity limiting the mechanical performance. In this work, using a commercial 3D-printer specimens of the polymer cellulose acetate (CA) were produced having porosities as low as 1–3 %. Quasi-static tensile tests demonstrate that these highly dense specimens reach similar or even higher strength values in comparison to their injection molded counterparts. The influence of the temperature management was studied by using different hot-ends, namely a standard one and a novel hot-end having a modified heat-block. Using the latter one, a homogeneous internal structure was achieved as observed with scanning electron microscopy (SEM). The very low porosities can be assigned to the elevated specimen temperature maintained during printing which is slightly above the materials glass transition temperature. Processing of CA at such temperatures leads to a slight loss of plasticizer as proved with NMR spectroscopy. This favorable change in material composition during printing additionally contributes to the mechanical strength of the test specimens. We conclude that the porosity is the key parameter (which has to be measured and minimized) to realize FFF components with good mechanical performance. Whereas we demonstrated FFF for the first time for CA as an industrially relevant thermoplastic material, our results can be easily applied to amorphous polymers in general. Graphical abstract: Image 1 Highlights: Highly dense printed specimens. Mechanical performance similar to injection molded counterparts. New hot end modification.